Cuentos continuos y dramatizaciones para desarrollar la expresión oral en niños y niñas de 5 años de la I.E N° 1847 de Conra - Santiago de Chuco - Urquizo Sarmiento, Flor Marina (2017)
The students of 5 years of the initial level of educational institution No. 1847 Conra hamlet of the district of Santiago de Chuco, showed difficulties in their orality, not expressed adequately and did not develop the capabilities of the area of communication in oral expression ._x000D_ The research is justified in the theoretical aspect because the knowledge of strategies to improve oral expression, allowed the students to improve their skills in terms of pronunciation, fluency, vocabulary, expressive resources and coherence in such a way that they learned to express easily their needs and interests and to use diverse expressive resources._x000D_ The objective was to use continuous stories and dramatization to achieve the learning of the oral expression competence in the area of Communication._x000D_ The theoretical underpinnings are related to the general and specific objectives of the different fields of action of the action research used._x000D_ The design used corresponds to the educational action research, consisting of the planning of the interventions according to hypothesis and action, whose purpose was the modification of the pedagogical practice in relation to the observed problem of 11 students of the initial level. The technique used in information processing was methodological, data and theoretical triangulation and reflection; using information gathering tools such as observation guide, field journals and checklist. Concluding that the good pedagogical practice is in the knowledge of the weaknesses and strengths of the student and teacher.